Supported ionic liquids for the efficient removal of acetylsalicylic acid from aqueous solutions - Bernardo, Sandra C. (2020)
Acetylsalicylic acid, commercially available as aspirin, is one of the most used drugs in the world, being detected in several environmental compartments, including drinking water supplies. Given its environmental impact, the development of a cost‐effective technology capable of removing this pharmaceutical from water samples is of high relevance, for which materials based on silica chemically modified with ionic liquids (SILs) can be foreseen as a promising alternative. In this work, four SILs (with the chloride anion and imidazolium or tetraalkylammonium cations of different alkyl side chain length) were synthesized and characterized, and their potential for the adsorption of acetylsalicylic acid appraised by adsorption kinetics and isotherms. Envisioning their use to treat drinking water, the toxicity of all SILs towards the liver cell line Hep2G was determined. The best identified SIL, comprising the dimethylbutylammonium cation, displays a maximum adsorption capacity of 0.08 mmol/g, being 1 g of this material sufficient to treat ca. 14,500 L of water containing 1 μg/L of acetylsalicylic acid (under ideal conditions). Furthermore, this material has a negligible toxicity towards the liver cell line Hep2G. The results obtained reinforce the potential of SILs as alternative adsorbents to effectively remove a cetylsalicylic acid from aqueous solutions, and may be envisioned as a promising strategy for the treatment of wastewater and drinking water.